Minat Penggunaan E-Wallet DANA di Kota Pontianak - Suhendry, Wendy (Jurnal Ekonomi Manajemen, 2021)
ABSTRACTThis study aims to determine the influence between perceived usefulness, perceived ease of use, perceived security, social influence, and promotion on intention to use DANA e-wallet. This research is an explanatory research using accidental sampling method combined with snowball sampling method. The variables of this study consist of independent variables, namely perceived usefulness, perceived ease of use, perceived security, social influence, and promotion, and the dependent variable, namely intention to use DANA e-wallet. The data analysis method used is multiple regression analysis with data collection through questionnaires in Pontianak. The results of this study are expected to contribute the development of consumer behavior theories in intention to use a technology, especially the factors that influence intention to use DANA e-wallet. The results of this study is the variables of perceived usefulness, perceived ease of use, perceived security, social influence, and promotion have an effect on the variable intention to use DANA e-wallet simultaneously. Partially, the variables that significantly influence the variable intention to use DANA e-wallet are perceived usefulness, perceived security, and promotion.Keywords: e-wallet DANA; Technology Acceptance Model; perceived security; social influence; promotion.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh antara faktor perceived usefulness, perceived ease of use, perceived security, social influence, dan promotion terhadap minat penggunaan e-wallet DANA. Penelitian ini termasuk jenis penelitian explanatory dengan menggunakan metode sampling aksidental yang dipadukan dengan metode snowball sampling. Variabel penelitian ini terdiri dari variabel bebas yaitu faktor perceived usefulness, perceived ease of use, perceived security, social influence, dan promotion dan variabel terikat yaitu minat penggunaan e-wallet DANA. Metode analisis data yang digunakan adalah analisis regresi berganda dengan pengumpulan data melalui kuesioner di kota Pontianak. Hasil penelitian ini diharapkan dapat berkontribusi dalam pengembangan teori-teori perilaku konsumen dalam minat penggunaan suatu teknologi khususnya faktor-faktor yang mempengaruhi minat penggunaan e-wallet DANA. Hasil penelitian ini adalah variabel perceived usefulness, perceived ease of use, perceived security, social influence, dan promotion berpengaruh terhadap variabel minat penggunaan e-wallet DANA secara simultan. Secara parsial variabel yang mempengaruhi variabel minat penggunaan e-wallet DANA secara signifikan adalah variabel perceived usefulness, perceived security, dan promotion.Kata Kunci: e-wallet DANA; Technology Acceptance Model; perceived security; social influence; promotion.